Development of Female Pelvic Medicine and Reconstructive Surgery Fellowship Programs following the Deadline for Senior Accreditation. Issue 4 (July 2018) - Polland, Allison; Richter, Lee A.
Abstract : Introduction : Female pelvic medicine and reconstructive surgery recently became a board‐certified subspecialty. Certification, available to urologists and gynecologists, requires completion of an accredited fellowship for residents graduating after 2010. We describe shifts in available training programs and applicants since this time. Methods : The National Resident Matching Program database was queried for "pelvic medicine and reconstructive surgery" from 2010 to 2016. Residency match data from the National Resident Matching Program and the American Urological Association matches during the same period were examined as a proxy for potential applicants. Linear regression was used to predict changes in number of programs and applicants through time. Results : Since 2010, there have been consistently more applicants than positions. The increase in obstetrics and gynecology programs has been greater than that in urology and combined programs. Despite this fact, there are far more obstetrics/gynecology than urology residency graduates each year, resulting in approximately 3 times the number of obstetrics/gynecology graduates per available fellowship position. Since 2010, only 1 obstetrics/gynecology position has gone unfilled, compared to 3 urology positions. Conclusions : While the female pelvic medicine and reconstructive surgery fellowship accreditation is designed for graduates of urology and gynecology, there are more programs designated as obstetrics/gynecology than as urology or combined, and obstetrics/gynecology programs are less likely to go unfilled. If urologists are to continue their role as an important part of the female pelvic medicine and reconstructive surgery workforce, we must encourage residents to pursue this career choice.